2020
DOI: 10.1039/d0ta04175k
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical transformation reaction of Cu–MnO in aqueous rechargeable zinc-ion batteries for high performance and long cycle life

Abstract: Rechargeable aqueous zinc-ion batteries (ZIBs) are emerging as alternative lithium-ion batteries for large-scale energy storage applications due to their safety and environmental friendliness. However, their applications are hindered by the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(50 citation statements)
references
References 53 publications
3
47
0
Order By: Relevance
“…12,46,47,51 It is worth noting that the capacity fluctuation phenomenon is ubiquitous in previously reported Mn-based ZIBs (Table S4, ESI †). 12,15,23,30,47,49,[51][52][53][54][55][56][57][58][59][60] For example, MnO xÀ2 reported by…”
Section: The Origin Of Capacity Fluctuation and New Capacity Evaluati...mentioning
confidence: 99%
“…12,46,47,51 It is worth noting that the capacity fluctuation phenomenon is ubiquitous in previously reported Mn-based ZIBs (Table S4, ESI †). 12,15,23,30,47,49,[51][52][53][54][55][56][57][58][59][60] For example, MnO xÀ2 reported by…”
Section: The Origin Of Capacity Fluctuation and New Capacity Evaluati...mentioning
confidence: 99%
“…So far, the most attention has been paid to Prussian blue analogues, manganese, vanadium, molybdenum, and organic cathode materials. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Among them, manganese-based compounds are considered as one of the most promising ones due to their competitive advantages of environment-friendliness, costeffectiveness, low toxicity, multiple valence states, and tunable structure/function. 3,4,14,18,27 Manganese oxides have been widely studied as zinc ion battery cathode materials and inspiring progress has been made.…”
Section: Introductionmentioning
confidence: 99%
“…3,4,14,18,27 Manganese oxides have been widely studied as zinc ion battery cathode materials and inspiring progress has been made. 4,14,[16][17][18][28][29][30][31] Most recently, MnS x , which is known as another important manganese-based compounds, has also been introduced in zinc ion batteries. 7,8,32,33 For instance, Chen et al activated Zn-inactive MnS by in situ electrochemically converting it into Mn oxides in zinc ion battery.…”
Section: Introductionmentioning
confidence: 99%
“…The electrostatic interaction between the Zn 2+ and MnO 2 frame is reduced by the presence of structural water, effectively promoting ion diffusion. 45,46 In this paper, it was found that structural water on the (102) and (110) crystal planes enhanced the electrochemical performance of zinc-ion batteries by improving the ion diffusion ability. The study on the introduction of structural water by wet-high-energy ball milling will provide a novel idea for the development of manganesebased oxide cathode materials.…”
Section: ■ Results and Discussionmentioning
confidence: 93%